Design of a Parallel and Distributed Network Security Simulation Platform - Songchang Jin; Songhe Jin; Shuqiang Yang; Xiang Zhu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
With the rapid development of computer science and technology, network attack and defense has become an important research topic in the field of information security. Teaching on network attack and defense technology in universities and research institutions has a very strong experimental characteristic, but due to the special nature and the destructive characteristic of network attack and defense technology, it is difficult to carry out experiments. In this paper, we designed and implemented a parallel and distributed network security experiments platform on which experiments can be carried out through a web interface and network simulation scripts. We believe that it is also an excellent platform for teaching courses in operating systems and networking. The results of experiments in this paper show that the platform could provide the laboratory personnels with independent experimental environment, perfect experimental control functions, excellent data collection and analysis services, etc. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2666